A theory of integrated gendered work evaluation (IGWE): A gender analysis of the unequal race for leadership through work evaluation of satisfaction and stress in Europe. Issue 3 (4th May 2021) - Moreno, Angeles; Fuentes Lara, Cristina; Tench, Ralph
ABSTRACT: This paper proposes the theory of integrated gendered work evaluation in public relations (IGWE). It holds that gender inequalities in the workplace are intrinsically linked to work-related evaluations, specifically measured through levels of satisfaction and stress. We theoretically place our proposal in the integrative phase of feminist theory that acknowledges the holistic nature of workers' lives and their commitment to fulfill not only their worker or employer roles but also their commitments to family and communities. The empirical contribution of this paper builds on past debates from two decades ago: the need for research to isolate factors that perpetuate gender discrimination. It explores factors of gender inequalities and conflicts that can affect the work-related evaluation of those people who make up the majority of the industry's employees: female public relations professionals. IGWE theory provides a new way of identifying, contextualizing, theorizing and analyzing how gender discriminations affect work evaluations combining both workplace and private life experiences from an integrated gender perspective.